2022
DOI: 10.1111/jomf.12846
|View full text |Cite
|
Sign up to set email alerts
|

Racial/ethnic variation in family support: African Americans, Black Caribbeans, and non‐Latino Whites

Abstract: Objective: This study examined racial and ethnic differences in the receipt and provision of instrumental family support. Background: Extended families provide significant levels of emotional and instrumental support across the life course. Despite their importance, extended family relationships and the assistance they provide are largely neglected in the literature. Further, questions remain concerning cultural variation in family support relationships and inconsistent findings on racial differences in family… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 51 publications
(91 reference statements)
0
10
0
Order By: Relevance
“…Finally, this study revealed important heterogeneity by household income within the Black adolescent sample, such that the link between providing support and educational outcomes emerged primarily (although not exclusively) in low‐income households. As such, the findings underscore the importance of investigating within‐group heterogeneity in family processes among Black adolescents (Cross, Taylor et al., 2018; Gaylord‐Harden et al., 2018; Taylor et al., 2022), particularly with attention to household socio‐economic status. In sum, this study points to family support as an important factor that relates to educational experience and outcomes of Black adolescents in the United States.…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…Finally, this study revealed important heterogeneity by household income within the Black adolescent sample, such that the link between providing support and educational outcomes emerged primarily (although not exclusively) in low‐income households. As such, the findings underscore the importance of investigating within‐group heterogeneity in family processes among Black adolescents (Cross, Taylor et al., 2018; Gaylord‐Harden et al., 2018; Taylor et al., 2022), particularly with attention to household socio‐economic status. In sum, this study points to family support as an important factor that relates to educational experience and outcomes of Black adolescents in the United States.…”
Section: Discussionmentioning
confidence: 83%
“…Supporting the family is a nearly universal feature of adolescents’ daily lives (Fuligni, 2019), including among Black adolescents in the United States (Cross, 2021; Cross, Nguyen et al., 2018; Taylor et al., 2022). Grounded in a strengths‐based approach (Fergus & Zimmerman, 2005) and drawing on a large, nationally‐representative sample, this study investigated how Black adolescents’ provision of different types of support to the family related to their educational outcomes, and whether this association differed for those living in low‐income compared to high‐income households.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations